Penggunaan Media Teknologi Informasi dan Gaya Belajar Terhadap Hasil Belajar Mata Pelajaran Bahasa Inggris - Adhityo Kuncoro; Dyah Rhetno Wardhani (Departement of Mathematics Education, 2022)
This research looks at how interactive multimedia influences learning outcomes in English, especially considering different learning styles. This research approach is a quantitative approach to the type of quasi-experimental research. The subjects of this study were class XII students at SMKN 7 Jakarta for the 2020/2021 academic year. This study used purposive cluster sampling to select two majors at SMKN 7 Jakarta, Graphic Design as the control group and Computer and Network Engineering as the experimental group, based on the characteristics of the departments. The number of students majoring in Graphic Design is 35 students while the Department of Computer and Network Engineering is 39 students. In the control group learning using sophisticated tools such as PowerPoint and media presentations the experimental group uses interactive multimedia learning tools such as flash. This research uses a quantitative approach because it is considered easier to analyze data using numbers so that it makes it easier to measure achievement. The results of this study indicate that interactive multimedia can be used to improve the English learning outcomes of students with different learning styles.